Pendekatan Fenomenologi: Pengantar Praktik Penelitian dalam Ilmu Sosial dan Komunikasi - Hasbiansyah, O (Mediator, 2008)
Phenomenology, initially, is a philosophy made popular by Edmund Husserl. Phenomenology, in essential, taught people to interact and learn more from phenomenon so that the meaning of reality, and the natural essence of reality, could be grasped by the observer. Phenomenology today develops as one of fundamental research method whose assumptions respect human uniqueness and subjective experiences. Phenomenon as experienced consciously by human was analyzed by two descriptions: textual description and scriptural description.